[PS 03-18] A SOCIO-EPIDEMIOLOGICAL STUDY OF HYPERTENSION AMONG INDIAN ADOLESCENTS. (September 2016) - Nair, Tapas Sadasivan; Garg, Suneela; Gupta, Vimal Kishore; Singh, Mongjam Meghachandra; Chandra, Lal
Abstract : Objective: To study the prevalence of hypertension and prehypertension among Indian adolescents and the associated risk factors. Design and method: A community based cross-sectional study was conducted over a period of one year in urban areas of central Delhi. 1005 adolescents were included in the study. The study was carried out by conducting house-to-house survey. The subjects selected were interviewed and tested for hypertension. Initially the purpose of the study was explained to each person in the local language. Written and informed consent was taken from parents and assent from subjects <18 years while written informed consent was taken from subjects ≥18 years. Subjects were interviewed using a predesigned, pretested, semi structured questionnaire. The collected data was analyzed using SPSS-PE-17 version. The factors significant in univariate analysis were considered in multivariate logistic regression analysis. Odds ratio and 95% confidence interval were used to quantify the risk factors. P value<0.05 was considered significant. Results: Overall prevalence of hypertension and prehypertension was 6.5% and 11.8% respectively. Prevalence of hypertension was significantly higher among higher age group [5–19 years] (p = 0.01), obese (p = 0.001), sedentary (p = 0.01) subjects, smokers (p = 0.01), non-vegetarians (p = 0.004) and those with family history of hypertension (p = 0.01). Independent risk factors on multivariate logistic regression analysis for hypertension were: age 15–19 yrs [OR = 3.31, CI:1.88–5.27], obesity [OR = 2.38. CI:1.41–4.02], non-vegetarian diet [OR = 1.79, CI:1.09–2.58], smoking [OR = 2.24, CI:1.61–3.72] and positive family history of hypertension [OR = 2.71, CI:1.79–4.58]. Conclusions: It is concluded from the present study that overall prevalence of hypertension and prehypertension was found to be 6.5% and 11.8% respectively. Prevalence of hypertension was higher among subjects of higher age group, obese, smokers, non-vegetarians and those with positive family history. Hence it is recommended that healthy lifestyle changes should be promoted to reduce the prevalence of hypertension. Intensive IEC campaigns are needed to educate adolescents about hypertension.